"Do More, Feel Better": Pilot RCT of Lay-Delivered Behavioral Activation for Depressed Senior Center Clients. Issue 3 (May 2022) - Raue, Patrick J.; Hawrilenko, Matt; Corey, Mariah; Lin, John; Chen, Shiyu; Mosser, Brittany A.
Highlights: Lay volunteers delivered "Do More, Feel Better" to fidelity standards. Clinical outcomes were comparable to professionally delivered Behavioral Activation. "Do More, Feel Better" can increase access to mental health care for older adults. Abstract: This pilot randomized control trial (RCT) tested "Do More, Feel Better" (DMFB), a lay-delivered Behavioral Activation intervention for depressed senior center clients. The study examined: (1) the feasibility of training older lay volunteers to fidelity; and (2) the acceptability, safety, and impact of the intervention. Twenty-one lay volunteers at four senior centers were trained in DMFB. Fifty-six depressed clients were randomized to receive 9 sessions of DMFB or Behavioral Activation delivered by social workers (MSW BA). Research assessments of overall client activity level (BADS) and depression severity (HAM-D) were conducted at baseline and Weeks 3, 6, and 9. Eighty-one percent of lay volunteers who underwent training were formally certified in DMFB. Depressed clients receiving each intervention reported high levels of satisfaction and showed large and clinically significant changes in 9-week activity level ( d ≥ 1.35) and depression severity ( d ≥ 3.34 ). Differences between treatment groups were very small for both activity level ( d MSW = 0.16; 95% CI, -0.70 to 1.02) and depression ( d MSW = 0.14; 95% CI, -0.63 to 0.91). Increases in activity level were associated with decreases in depression (β = -0.42; 95% CI, -0.55 to -0.30). Both interventions appeared to work as intended by increasing activity level and reducing depression severity. "Do More, Feel Better" shows the potential of evidence-based behavioral interventions delivered by supervised lay volunteers, and can help address the insufficient workforce available to meet the mental health needs of community-dwelling older adults.